Respuestas

  • Usuario de Brainly
2012-07-20T06:48:02+02:00

(-1)3+(-1)4=

-3 -4 = 12

 

4-2= 2

 

[(-3)2]3=

(-6) 3  = -18

 

[(-2)2]3= (-4) 3 = -12

 

[-(2)3]2= (-6) 2 = -12

 

(-2)-2.(-2)2= -4 x -4 = 16

 

(-1)-9.(o,25)-3.(8)-2=

18 x -0,75 x -16

-288 x 0,75

-216

 

[(-3)4]0,75=

(-12) 0,75

-9

Saludos,

jvilchez

2012-07-20T07:24:23+02:00

(-1)3+(-1)4=

-1+3-1+4=

7-1=6

 

4-2= 2

 

[(-3)2]3=

-3+2+3=

-3+5=2

 

[(-2)2]3=

-2+2+3=

-2+5=3

 

[-(2)3]2=

-2+3+2=

-2+5=3

 

(-2)-2.(-2)2=

-2+4+2=

-2+6=4

 

(-1)-9.(o,25)-3.(8)-2=

-1-2.25-24-2=

-29.25


[(-3)4]0,75=

-3+4+0.75=

-3+4.75=1.75